The design of Forecasting for Medicine Demand at Health Centre (Puskesmas) I Toili, Moilong District, Centre Sulawesi Province - Putra, Andri Pratama; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Health centre (Puskesmas) I Toili has several health services, one of them is the apotek. The problem with apotek is when restocking medicines, the pharmacist does not know exactly the demand of medicine for the next periode resulting cumulation of medicines that have not yet been sold. Other than that, the phartmacist when selling the medicines sometime does not paying attention on the expire date. The solution for the problems that has been described is to create a program for forecasting demand for the medicine consisting of: forecasting demand for medicine with Double Exponential Smoothing (DES) methode, medicine sale with First Expider Firs Out (FEFO) methode. The result of this research has shown that the program has able to do forecast for medicine demand using (DES), to save the sales of medicine with FEFO methode and medicine restock report, medicine forecast, and the sales of medicine, presented on chart with high accuracy and fast.